Evaluating the effectiveness of the organizational process design-oriented company "price-quality-profit" - Хімічева, Ганна Іванівна; Грицай, Алла Володимирівна; Колесіна, Наталія Василівна (Eastern-European Journal of Enterprise Technologies, 2011)
For the effective functioning of project-oriented companies need in real time to determine the effectiveness of current organizational processes. The article deals with mechanisms that allow the procedure to assess the format of “cost-quality-profit”